Aktiviti ekonomi sempadan di Perairan Sg. Golok - Rantau Panjang: Isu dan cabaran - Hussin, Fauzi; Abdullah, Norehan; Abdullah, Hussin; Maamor, Selamah (2013)
Sungai Golok waters of about 29.9 kilometers from Pengkalan Kubor, Tumpat to Rantau Panjang, Kelantan (Malaysia) became the main boundary that separates the state of Kelantan (Malaysia) with Narathiwat province(Thailand). There are difficulties faced by security personnel from specific agencies manning the border along the waters of Sungai Golok and Rantau Panjang duty-free zone.In terms of border enforcement in the waters of Sungai Golok and Rantau Panjang duty-free zone is found there are various difficulties faced by security personnel from specific agencies. Although there are security personnel such as the Anti-Smuggling Unit (UPP), Customs Unit (the enforcement), and military (replacing the General Operations Force task) that controls the entry and exit of illegal goods through Sungai Golok waters to / from Rantau Panjang duty-free zone, but the entry of goods illegal is still going on.This paper will discuss the issues and challenges faced by security personnel to control the smuggling of illegal goods along the waters of Sungai Golok and Rantau Panjang duty-free zone and discuss several proposals to overcome the problem of smuggling.The interview is in the form of focus groups involving officials of law enforcement agencies was conducted to gather information.